Factors Affecting the Accuracy of Operation of the Electrohydraulic Actuation Position System With Throttling Control - Nauparac, Dragan; Višnjić, Nemanja (International Conference Fluid Power 2025: Conference Proceedings, 2025)
The paper analyses most of the factors that influence the positioning error in the stationary mode of the electrohydraulic positional actuation systems and several ways to calculate the positioning accuracy in relation to the considered factors that influence the accuracy. Criteria are defined so that it is possible to check whether the desired accuracy of positioning can be achieved in the early design phase, but also the repeatability of accuracy over the full range of positioning. This is important to know, i.e. to define in the early design phase in relation to the basic limit performance of the actuation system, above all in relation to the bandwidth of the actuation system and to see if there are possibilities for algorithmic and/or structural correction of the positioning accuracy of the actuation system in the later stages of design. It starts from the basic 3-order linearized model, but in the analysis, factors of unmodeled dynamics are added in the 3-order linear model.